2018
DOI: 10.4103/aja.aja_17_17
|View full text |Cite
|
Sign up to set email alerts
|

The role of the serum testosterone levels as a predictor of prostate cancer in patients with atypical small acinar proliferation at the first prostate biopsy

Abstract: The current literature does not support the usefulness of clinical markers on predicting which patients with atypical small acinar proliferation (ASAP) are more likely to progress to prostate cancer (PCa). Androgens have long been considered to be the potential risk factors for PCa. However, the role of testosterone is controversial. The present study aims to analyze the relationship between serum testosterone (TS) levels and the diagnosis of PCa after a first prostate biopsy in patients affected by ASAP. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Dell'Atti et al. [ 45 ] reported that serum testosterone levels change significantly on patients with a confirmed diagnosis of prostate cancer on the second biopsy who were previously found with atypical small acinar proliferation during the first biopsy performed 6 months prior. The next step following the findings of this study should focus on evaluating the serum level of DHT and estradiol among BPH patients and their association with prostate volume.…”
Section: Discussionmentioning
confidence: 99%
“…Dell'Atti et al. [ 45 ] reported that serum testosterone levels change significantly on patients with a confirmed diagnosis of prostate cancer on the second biopsy who were previously found with atypical small acinar proliferation during the first biopsy performed 6 months prior. The next step following the findings of this study should focus on evaluating the serum level of DHT and estradiol among BPH patients and their association with prostate volume.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5% of prostate biopsies are diagnosed as ASAP due to the absence of adequate histomorphological parameters allowing differentiation of the atypical focus from PCa [ 8 ]. In this study, the ASAP rate was consistent with that in the literature (5.67%) [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate growth and differentiation are closely related to the dihydrotestosterone level. PCa patients with a smaller prostate volume have lower levels of testosterone and dihydrotestosterone and a limited secretion of prostatic growth factors, such as insulin and insulin-like growth factor ( 29 ). The low expression of these hormones results in a more adverse microenvironment, where only more invasive tumor cells can grow, and the occurrence of high-grade PCa may be promoted.…”
Section: Discussionmentioning
confidence: 99%